Design and simulation of triple metal double-gate germanium on insulator vertical tunnel field effect transistor. (August 2021) - Chawla, Tulika; Khosla, Mamta; Raj, Balwinder
Abstract: In this paper, a novel Triple metal double gate germanium on insulator vertical TFET is proposed and investigated by using SILVACO ATLAS TCAD tool. Gate metal work-function engineering is used to overcome the problem of low ON-current, high OFF-current, high average subthreshold swing and low ION /IOFF ratio which are present in single material double gate TFET. By modulating the values of metal gate work-functions, the performance of the device is improved. The low band-gap material and vertical tunneling concept also increase the steepness of subthreshold slope as well as ON-current of the device. Further the effects of channel length and gate to source overlap thickness on the device are also analysed to get optimum device dimensions for obtaining the improved performance results. The vertical stacking of source, channel and drain also consumes less space as compared to the conventional TFETs. So, the considerable good performance of this proposed device makes it suitable as an attractive choice for ultra-low power applications.